The promise of the nation gender, history, and nationalism in contemporary Ilokano literature - Galam, Roderick G. (Quezon City Ateneo de Manila University Press, 2008)
"The Promise of the Nation examines the construction of the nation in contemporary Ilokano literature in the intersections of gender, history, and nationalism by tracing Ilokano literature's political, material and socio-cultural connections and examining its intervention in Philippine socio-political discourse, history, and historiography. It attends to and addresses the limitations, contradictions and potential constituting Ilokano writers' efforts to (re)make a Filipino nation, efforts made in the context of Spanish and American imperialism, neocolonialism, martial law, militarization, urban squatting, patriarchy, migrant work, and the marginalization of ethnic peoples. Finally, the book argues that the writers' project of realizing what Caroline Hau has evocatively called the nation's "promise of community" may be more powerfully imagined and grasped were nationalism transformed by feminism; indeed if we dream this nation, see and seek its promise and possibility with a feminist-communitarian imagination.
Part I. Toward feminist nationalism -- Chapter 1. Who's imagining community? -- Part II. National redemption -- Chapter 2. Self-determination : history and the recovery of the national soul-body in Juan S. P. Hidalgo's Saksi ti Kaunggan -- Chapter 3. Writing Finis to US Imperialism : history, nation, and national redemption in Reynaldo Duque's Angkel Sam -- Part III. The state of the nation -- Chapter 4. State of domination : gender, class, and the rule of law in Jose Bragado's Gil-ayab ti Daga -- Chapter 5. The United Nation-state : gender, militarization, and patriarchy in Clensecio Rambaud's Dagiti Bin-i ti Kimat -- Part IV. Toward the promise of nationhood -- Chapter 6. Rescuing history for the nation : the nationalizing imagination in Bernardino Alzate's Alsa Masa 1763 -- Chapter 7. A poetic cartography of the promise of the nation : Hermilinda Lingabaoan-Bulong?s poetry -- Conclusion. Toward a feminist-communitarian imagination -- Notes -- Bibliography -- Index.
Revision of the author's thesis (M.A. Comparative Literature : Regional and National Literatures)--University of the Philippines, Diliman.
Keywords: Literature and society -- Philippines; Nationalism in literature; Nationalism and feminism -- Philippines; Iloko literature -- Social aspects; Iloko literature -- History and criticism